Hellenistic Ash Containers from Phoinike (Albania) - Aleotti, Nadia (Journal of Hellenistic Pottery and Material Culture, 2016)
The paper focuses on the Hellenistic ash containers from the cemetery of Phoinike, investigated by the University of Bologna and the Albanian Institute of Archaeology from 2001 to 2009. This study was conducted by analyzing the containers from two different points of view: the study of their shapes and their chronological evolution on the one hand, and on the other their contribution to the investigation of funerary ideology at Phoinike. For this inquiry the analogies between grave goods and connections between sex, grave goods and ash containers were studied.